FORMULASI PASTA SERBUK KOPI DENGAN VARIASI KONSENTRASI SEBAGAI DAYA HAMBAT TERHADAP BAKTERI STAPHYLOCOCCUS AUREUS - Viani Anggi (Jurnal Farmasi UIN Alauddin Makassar, 2016)
Formulation have been conducted Pasta coffee powder with variation concentration Southwestern As inhibitory against Staphylococcus aureuss, this study to determine whether the coffee powder can be formulated into a paste and to determine which are most effective concentration to inhibit the growth of Staphylococcus aureus. Pasta coffee powder made by vary the concentration of coffee powder that is Formula I, II, III, and IV with coffee beans concentration 0%, 30%, 35%, and 40% were tested on inhibition against Staphylococcus aureus using the diffusion method with filter paper. From the results of this study indicate that coffee powder can be formulated into dosage pasta and able to inhibit the growth of Staphylococcus aureus, the results of the statistical Ansira test result that of formula I, formula II, formula III and formula IV there are significant differences. The results were further using HSD test showed that the concentration of 30% most effectively inhibit the growth of Staphylococcus aureus.